Housing Policy Reforms in Post-Socialist Europe Lost in Transition - Tsenkova, Sasha (Contributions to Economics, 2009)
The book provides unique insights into the process of housing reforms in post-socialist Europe during its transition to markets and democracy. It explores the relationships between housing policy and housing system performance in nine countries: Albania, Bulgaria, Bosnia and Herzegovina, Croatia, Former Yugoslav Republic of Macedonia, Romania, Republic of Moldova, Serbia and Montenegro. The research captures important housing policy and market dynamics producing tangible outcomes of the transition processes. Using a comparative framework for analysis and evaluation, the book provides an enduring and sound illustration of the post-socialialist experience highlighting patterns of diversity, complexity and institutional transformation in the new path-dependent housing systems in the region. The research is driven by the premise that housing policy matters and that better policies lead to more efficient housing system performance. The book provides a rich framework for evaluation of housing reforms in a dynamic region. Well written, subtle and insightful, it will set the terms of the debate on transition in housing for years to come... a must read. Dr Robert Buckley, Rockefeller Foundation, New York, USA This is an excellent and very systematic account of housing reforms, housing systems and housing policies in post-socialist Europe. An important piece of work bringing new ideas and new arguments for housing policy research in a very challenging way. Professor Ronald van Kempen, Utrecht University, the Netherlands The author is amazingly knowledgeable about housing issues across transition economies and the book provide extremely useful and comprehensive analysis of both the problems encountered and the policies implemented. Professor Christine Whitehead, London School of Economics, UK This book provides a thorough and systematic review of the housing systems of South East Europe. It is a valuable source book and a powerful evaluation that demonstrates beyond doubt that 'housing policy matters'. Professor Mark Stephens, Centre for Housing Policy, University of York, UK.